Correlation between microstructure of TiO2-anatase precursor and lithium storage properties of hydrothermally synthesized TiO2-B. (May 2019) - Opra, Denis P.; Gnedenkov, Sergey V.; Sokolov, Alexander A.; Mayorov, Vitaliy Yu.; Sinebryukhov, Sergey L.
Abstract: TiO2 -B nanobelts have been synthesized by hydrothermal route using TiO2 -anatase precursors with different microstructure. The decrease in average size of starting product improves the degree of TiO2 -B crystallinity and increases the surface area. Both of them strongly influence on the electrochemical performance of as-prepared TiO2 -B: the capacity of 203 mAh g −1 is still maintained after 35 cycles, with a degradation of 0.25% per cycle for material synthesized using TiO2 -anatase phase with a particle size of 25 nm. Oppositely, the samples obtained from larger particles show poorer lithium storage with a worse capacity retention. Graphical abstract: Unlabelled Image